To Develop and Evaluate the Effectiveness of Educational Package on Life-Skilltraining on the Life-Skill Practices among Substanceabusers of a Selected Drug- Rehabilitation Centre, New Delhi (International Journal of Psychiatric Nursing, 2022)
Background: Substance Abuse is a phenomenon in the world and has invaded the human society as themost important social damage. Substance abuse is a nonadaptive model of drug use which results in advanceproblem and consequences , and includes a set of cognitive , behavioural , and psychological symptoms1.Methods: It was a Quasi Experimental study, total 60 substance abusers were selected ( 30 samples eachfor experimental and control group) by using convenient sampling technique. Structured questionnaire wasused to collect the demographic characteristics & to assess the level of life skill practices of substanceabusers residing in rehabilitation centre for both experimental and control group, followed by administrationof Life skill training program for experimental group only.Results: The findings of the study revealed that difference between pre-test and post-test life skill score‘t’ value was 14.57 for degree of (39) at 0.05 level of significance. This shows that there was significantincrease in life skill practices of substance abusers after administration of Life skill training programme. Thepost-test mean life skill practice score of experimental group and post-test mean life skill practice score ofcontrol group shows ‘t’ value of 11.316 for the degree of freedom (78) at 0.05 level of significance.Conclusion: Human society has been challenged with Substance abuse and sustained notable ﬁnancial andspiritual losses. The problem of abuse is one of the topfour world crises and the main social crisis in India.The findings of study reveals that there was significant increase in life skill practices of experimental groupthan the control group after administration of Life skill training programme1.
Keywords: Life skill, Life skill training programme, Substance abusers